Factors Affecting Energy Demand in Developing Countries: A Dynamic Panel Analysis - Aziz, Azlina Abd.; Nik Mustapha, Nik Hashim; Ismail, Roslina (International Journal of Energy Economics and Policy, 2013)
This work presents an empirical study of energy demand, in which demand for energy is expressed as a function of various factors, such as income, price, economic structure, and CO2 emission. Parameter values are estimated econometrically, using a panel data approach of 16 developing countries over 30-years period. In general, the empirical results of this study confirm the majority of the findings in energy demand analysis where income and price have shown to be important determinants in energy demand. Moreover, economic structure and also CO2 emission appear to exert significant impact on energy demand. Short- and long-run elasticities of demand are estimated and some policy suggestions are given to improve energy saving and green energy consumption in developing countries. Keywords: Energy demand; panel data JEL Classifications: C23; Q31; Q41